Digital Marketing Strategy to Build Brand Awareness of the SiCepat Express During the COVID-19 Pandemic - Anandita, Risa; ., Habibi; Bin Amsar, Arziman; Lukiyanto, Kukuh (KnE Social Sciences, 2024)
Online shopping boomed during the COVID-19 pandemic, leading to a major growth of shipping company businesses. As such, shipping companies needed to have a good marketing strategy to maintain brand existence and survive in the midst of competition. The purpose of this study was to analyze the marketing strategy implemented by SiCepat Ekspres in building brand awareness during the COVID-19 pandemic. This study used a qualitative method. The results of this study showed that SiCepat Ekspres built brand awareness using the Customer Loyalty Program strategy, supported CSR, promos, and also digital marketing such as YouTube and Instagram, and started switching to the TikTok platform due to increased traffic during the COVID-19 pandemic. The benefit of the results is to consider decision-making to increase brand awareness through implementing marketing strategies that are in line with the company’s targets; besides that, for further research, it can be used as a guide and reference for similar research topics. Keywords: digital marketing, brand awareness, COVID-19